Concerted and sequential three-body fragmentation of deep-core-ionized carbon disulfide. Issue 1 (9th December 2022) - Guillemin, R.; Marin, T.; Zmerli, M.; Bomme, C.; Ismail, I.; Journel, L.; Marchenko, T.; Travnikova, O.; Piancastelli, M. N.; Simon, M.
Abstract : Momentum vector correlation is a powerful tool to study molecular dissociation. Abstract : Momentum vector correlation is a powerful tool to study molecular dissociation. We have studied the three-body fragmentation of carbon disulfide after sulfur 1s photoionization by means of momentum imaging techniques. Concerted and sequential pathways are disentangled in three-body fragmentation using adapted analysis strategies. In particular, we introduce various data visualization schemes that are proved to be particularly efficient to determine dissociation dynamics.